Errors Analysis in Using Simple Past Tense in Nursing Students’ Writing Assignments - Situmorang, Komilie; Santa Maya Pramusita (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2024)
Nursing students learn General English (GE) to prepare them to study English for Nursing as their core subject. The primary goal of GE is to prepare them to be able to talk about daily topics and grammar points including simple past tense which was taught implicitly. In fact, teaching grammar is assumed to be trivial lately as teachers shift to more into English teaching trends. Therefore, it is important to go to the root and find ways to help students with their grammar struggle. This study seeks to find the nursing students’ error in simple past tense through scrutinizing their writing and thus can evaluate the teaching grammar method. The methodology was descriptive quantitative where 50 students’ writing assignments were the data. The errors were identified in the table and were classified based on the error types based on Duly’s surface strategy taxonomy. The errors were then analysed quantitatively to find percentages of the errors. The excerpts from the students’ writing were included in the result to support the analysis. The findings indicate that mis-formation were the biggest errors with 57.59%, mis-ordering with 20.98%, addition with 12.95%, and omission with the smallest error with 8.48%. The analysis indicates that the interlingual and intralingual transfer contribute to these errors made. Thus, there needs to be a reflection on the grammar teaching done in nursing students now. Teachers should focus on helping the students with their grammar difficulties and flexibly switch the teaching implicitly and explicitly to suit the students need.